Method for improving crystallinity of molecular sieve

By adjusting the alkali ratio and temperature during the crystallization process of the molecular sieve, providing crystallization power, the problem of low crystallinity of the molecular sieve is solved, and efficient crystallinity improvement and stability improvement are achieved.

CN119160910AActive Publication Date: 2024-12-20CHALCO SHANDONG NEW MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411297399.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the crystallinity of the molecular sieve, resulting in the attenuation of its adsorption performance after regeneration, the reuse is limited, and the crystallinity is difficult to stabilize at least 90%.

Method used

During the crystallization process of the molecular sieve, the first sodium aluminosilicate gel slurry is crystallized and the alkali ratio is adjusted to form a second sodium aluminosilicate gel slurry with a target alkali ratio, and then the alkaline ratio is adjusted. The second crystallization is performed to provide crystallization power to improve crystallinity.

Benefits of technology

The crystallinity of molecular sieve has been significantly improved, stably reaching more than 90%, extending its reuse times and simplifying the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160910A_ABST
    Figure CN119160910A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the crystallinity of a molecular sieve, and the method comprises the following steps: carrying out first crystallization on first sodium aluminosilicate gel slurry, and adding alkali liquor into the first sodium aluminosilicate gel slurry when the first sodium aluminosilicate gel slurry is crystallized to the first crystallinity, so as to obtain second sodium aluminosilicate gel slurry with a target alkali ratio; and performing second crystallization on the second sodium aluminosilicate gel slurry to obtain the molecular sieve. When the first sodium aluminosilicate gel slurry is crystallized to a first crystallinity, adding alkali liquor into the first sodium aluminosilicate gel slurry so as to inject new crystallization power into the first sodium aluminosilicate gel slurry system, so that the crystallinity of the molecular sieve is improved; and performing second crystallization on the second sodium aluminosilicate gel slurry with the target alkali ratio to further provide crystallization power for improving the crystallinity so as to obtain the molecular sieve with high crystallinity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of molecular sieve preparation, and in particular to a method for improving the crystallinity of molecular sieves. Background Art

[0002] Molecular sieves are widely used in industries such as chemical, electronics, petrochemical, and natural gas. Molecular sieves have the ability to dry gases such as air, hydrogen, oxygen, nitrogen, and argon. In industrial production, two sets of adsorption dryers are generally connected in parallel, and one can be regenerated while the other is working. They work and regenerate alternately to ensure continuous operation of the equipment. The dryer works at room temperature and is regenerated by flushing air at a temperature of 350°C. The number of times the molecular sieve is regenerated and reused is generally determined by the crystallinity of the original molecular sieve powder. The higher the crystallinity of the original molecular sieve powder, the smaller the attenuation of its adsorption performance after regeneration, and the more times it can be reused.

[0003] At present, the control of the crystallinity of molecular sieve raw powder generally adopts measures such as using higher purity aluminum and silicon sources, more precise control of synthesis ratio and temperature, and narrowing the crystallization temperature range. Even so, the crystallinity of molecular sieve raw powder still fluctuates greatly and it is difficult to stably reach more than 90%. Summary of the invention

[0004] The present application provides a method for improving the crystallinity of molecular sieves to solve the following technical problem: how to improve the crystallinity of molecular sieves.

[0005] In a first aspect, the present application provides a method for improving the crystallinity of a molecular sieve, the method comprising:

[0006] Performing a first crystallization on the first sodium aluminosilicate gel slurry until the crystallization reaches a first degree of crystallinity, and then adding an alkali solution to the first sodium aluminosilicate gel slurry to obtain a second sodium aluminosilicate gel slurry having a target alkali ratio;

[0007] The second sodium aluminosilicate gel slurry is subjected to a second crystallization to obtain a molecular sieve.

[0008] Optionally, the first crystallinity is 75% to 80%.

[0009] Optionally, the second crystallization temperature is 95°C to 100°C.

[0010] Optionally, the first crystallization temperature is 80°C to 85°C.

[0011] Optionally, the alkali solution includes sodium hydroxide solution.

[0012] Optionally, the content of Na2O in the sodium hydroxide solution is 100g / L to 110g / L.

[0013] Optionally, the molecular sieve includes one of the following: 4A molecular sieve and 13X molecular sieve.

[0014] Optionally, if the molecular sieve is a 4A molecular sieve, the target alkali ratio is less than 3.0.

[0015] Optionally, if the molecular sieve is a 13X molecular sieve, the target alkali ratio is less than 3.5.

[0016] Optionally, the method further comprises: chemically reacting the silicon source solution and the aluminum source solution to obtain the first sodium aluminosilicate gel slurry.

[0017] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0018] The method for improving the crystallinity of the molecular sieve provided in the embodiment of the present application comprises: subjecting the first sodium aluminosilicate gel slurry to a first crystallization, until the crystallization reaches the first crystallinity, adding alkali solution to the first sodium aluminosilicate gel slurry to obtain a second sodium aluminosilicate gel slurry having a target alkali ratio; subjecting the second sodium aluminosilicate gel slurry to a second crystallization to obtain a molecular sieve. The molecular sieve consumes a large amount of alkali during the crystallization process, that is, the residual alkali concentration in the mother liquor decreases as the crystallization proceeds, resulting in a problem of insufficient crystallization power due to the decrease in alkali concentration in the later stage of crystallization, which affects the improvement of the crystallinity of the molecular sieve product. Therefore, when the first sodium aluminosilicate gel slurry is liquid-crystallized to the first crystallinity, alkali solution is added to the first sodium aluminosilicate gel slurry, thereby injecting new crystallization power into the first sodium aluminosilicate gel slurry system, thereby improving the crystallinity of the molecular sieve; the second sodium aluminosilicate gel slurry having a target alkali ratio undergoes a second crystallization, further providing crystallization power for improving the crystallinity, thereby obtaining a molecular sieve with high crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0021] Figure 1 A schematic flow chart of a method for improving the crystallinity of a molecular sieve provided in an embodiment of the present application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0023] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0024] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0026] Molecular sieve is a kind of aluminosilicate compound with cubic lattice, mainly composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, connected by oxygen bridges to form an open skeleton structure, in which there are many channels with uniform pore size and neatly arranged holes with large internal surface area. In addition, it also contains metal ions with low valence and large ion radius and water in chemical state. Because water molecules are continuously lost after heating, but the crystal skeleton structure remains unchanged, many cavities of the same size are formed, and the cavities are connected by many micropores of the same diameter. These tiny holes have uniform diameters and can adsorb molecules smaller than the diameter of the holes into the inside of the holes, while repelling molecules larger than the holes. Therefore, molecules of different diameters can be separated like a sieve, that is, it has the function of "sieving" molecules, so it is called molecular sieve. At present, molecular sieves are widely used in chemical, electronic, petrochemical, natural gas and other industries.

[0027] At present, the control of the crystallinity of molecular sieve raw powder generally adopts measures such as using higher purity aluminum and silicon sources, more accurately controlling the synthesis ratio and temperature, and narrowing the crystallization temperature range. Even so, the crystallinity of molecular sieve raw powder still fluctuates greatly, and it is difficult to stably reach more than 90%. The main factor affecting the crystallinity is the lack of power during the crystal growth process. During the growth of crystals, there is a process of dissolution-crystallization-redissolution-recrystallization. In this process, some deformed crystals will be dissolved and recrystallized. However, when the crystallization process is carried out under a lower power, due to insufficient power, this process will become long and incomplete. Therefore, in response to this problem, the applicant has found through a large number of experiments that when the crystallization process enters a certain stage of dissolution-crystallization, new crystallization power is injected into the system to accelerate the dissolution-crystallization process. When properly controlled, the crystallinity of the molecular sieve will be greatly improved. Therefore, in the first aspect, the present application provides a method for improving the crystallinity of molecular sieves, Figure 1 A schematic diagram of a method for improving the crystallinity of a molecular sieve provided in an embodiment of the present application; see Figure 1 , the method comprising:

[0028] S1, subjecting the first sodium aluminosilicate gel slurry to a first crystallization, until the crystallization reaches a first degree of crystallinity, adding an alkali solution to the first sodium aluminosilicate gel slurry to obtain a second sodium aluminosilicate gel slurry having a target alkali ratio;

[0029] In some embodiments, the first crystallinity is 75% to 80%.

[0030] In the embodiment of the present application, the first sodium aluminosilicate gel slurry is subjected to the first crystallization, and when it is crystallized to the first crystallinity, alkali solution is added to the first sodium aluminosilicate gel slurry, and the first crystallinity can be 75% to 80%. The reason is that: within the numerical range of the first crystallinity, the mother liquor lacks the power of crystallization at this time. The addition of alkali solution at this time can provide the system with alkali concentration, and provide sufficient alkali concentration for the later stage of crystallization, so as to avoid the problem of insufficient alkali causing insufficient crystallization power, which affects the improvement of product crystallinity; the alkali concentration in the mother liquor before the first crystallinity is 75% can meet the crystallization requirements, and after the first crystallinity is 80%, even if alkali solution is added, it is difficult to improve the crystallinity. Exemplarily, the above-mentioned first crystallinity can be 75%, 76%, 77%, 78%, 79%, 80%, etc.

[0031] In some embodiments, the first crystallization temperature is 80°C to 85°C.

[0032] In the embodiment of the present application, the first sodium aluminosilicate gel slurry is first crystallized at a first crystallization temperature of 80°C to 85°C, so that the crystallization process can be uniform and the consistency and stability of the crystallization can be ensured. Exemplarily, the first crystallization temperature can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, etc.

[0033] In some embodiments, the alkaline solution includes sodium hydroxide solution.

[0034] In some embodiments, the content of Na2O in the sodium hydroxide solution is 100 g / L to 110 g / L.

[0035] In the embodiment of the present application, the alkali solution can be a sodium hydroxide solution, and the content of Na2O in the sodium hydroxide solution can be 100g / L to 110g / L. The reason is that when the sodium hydroxide solution is added to the slurry, there will be a risk of crystallization due to uneven mixing. In order to avoid the occurrence of this risk, it is more reasonable to adjust the concentration of the sodium hydroxide solution to 100g / L to 110g / L characterized by Na2O. At the same time, it also avoids the sodium hydroxide solution concentration being too low, resulting in the solid content of the dilution system and causing a decrease in production efficiency. Exemplarily, the content of Na2O in the above-mentioned sodium hydroxide solution can be 100g / L, 101g / L, 102g / L, 103g / L, 104g / L, 105g / L, 106g / L, 107g / L, 108g / L, 109g / L, 110g / L, etc.

[0036] In some embodiments, the molecular sieve includes one of the following: 4A molecular sieve, 13X molecular sieve.

[0037] In some embodiments, if the molecular sieve is 4A molecular sieve, the target alkali ratio (molar ratio of sodium oxide to aluminum oxide in the slurry system) is less than 3.0.

[0038] In some embodiments, if the molecular sieve is a 13X molecular sieve, the target base ratio is less than 3.5.

[0039] In the embodiment of the present application, the crystallinity of 4A zeolite molecular sieve and 13X zeolite molecular sieve is closely related to the thermal stability of these two products. The higher the crystallinity, the higher the thermal stability, which is conducive to the molding and roasting of molecular sieve products. The crystallization of 4A zeolite molecular sieve and 13X zeolite molecular sieve is the process of converting gel into crystals. This process requires power. There are two sources of power, one is the temperature during crystallization, and the other is the concentration of excess alkali. Therefore, the target alkali ratio of 4A molecular sieve is set to be less than 3.0; the target alkali ratio of 13X molecular sieve is less than 3.5, to ensure that sufficient alkali concentration is provided for the second crystallization process, thereby providing sufficient power for the second crystallization, improving the crystallinity of the target molecular sieve product, and at the same time, while meeting the alkali concentration required for crystallization to the greatest extent, avoiding the situation where the crystallization affects other indicators of the product. For example, if the molecular sieve is 4A molecular sieve, the target alkali ratio may be 2.8, 2.7, 2.6, 2.5, 2.4, etc.; if the molecular sieve is 13X molecular sieve, the target alkali ratio may be 3.3, 3.1, 3.2, 3.1, 3.0, etc.

[0040] In some embodiments, the method further includes: S0, chemically reacting the silicon source solution and the aluminum source solution to obtain the first sodium aluminosilicate gel slurry.

[0041] In the embodiment of the present application, the first sodium aluminosilicate gel slurry is obtained by chemically reacting a silicon source solution and an aluminum source solution. Exemplarily, water glass and a sodium aluminate solution are chemically reacted to obtain the first sodium aluminosilicate gel slurry.

[0042] S2. subjecting the second sodium aluminosilicate gel slurry to a second crystallization to obtain a molecular sieve.

[0043] In some embodiments, the second crystallization temperature is 95°C to 100°C.

[0044] In the present application embodiment, the crystallization of 4A zeolite molecular sieve and 13X zeolite molecular sieve is the process of converting gel into crystals, which requires power. There are two sources of power, one is the temperature during crystallization, and the other is the concentration of excess alkali. The second sodium aluminosilicate gel slurry with a target alkali ratio satisfies the concentration of excess alkali, while increasing the temperature of the second crystallization. The temperature during crystallization cooperates with the concentration of excess alkali to maximize the crystallinity of the molecular sieve. Exemplary, the temperature of the above-mentioned second crystallization can be 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc. In addition, after the crystallization is completed, separation, washing, and drying are performed to obtain a high-crystallinity molecular sieve product.

[0045] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0046] Example 1

[0047] The water glass with a concentration of SiO2: 16.79% and Na2O: 5.5% and the sodium aluminate solution with a concentration of Al2O3: 92.3g / L and Nk: 119.7g / L are synthesized according to a silicon-aluminum ratio of 2.0, and the synthetic alkali ratio is 2.7 to obtain a first sodium aluminosilicate gel slurry;

[0048] After the first crystallization at the first crystallization temperature of 70°C for 5 hours, the crystallinity was 75.4%. A sodium hydroxide solution with a concentration of Na2O: 102.3 g / L was added to adjust the synthetic alkali ratio to 2.95;

[0049] The temperature is raised twice for the second crystallization, and the material is discharged after the second crystallization at the second crystallization temperature of 97° C. for 2 hours, and the 4A molecular sieve product is obtained after separation, washing and drying. The crystallinity of the 4A molecular sieve product in Example 1 is 93.6%.

[0050] Example 2

[0051] The water glass with a concentration of SiO2: 15.29% and Na2O: 5.9% and the sodium aluminate solution with a concentration of Al2O3: 30.2g / L and Nk: 32.8g / L are synthesized according to a silicon-aluminum ratio of 2.8, and the synthetic alkali ratio is 2.8 to obtain a first sodium aluminosilicate gel slurry;

[0052] After the first crystallization at the first crystallization temperature of 70°C for 12 hours, the crystallinity was 77.1%. A sodium hydroxide solution with a concentration of Na2O: 106.7 g / L was added to adjust the synthetic alkali ratio to 3.3 to obtain a second sodium aluminosilicate gel slurry;

[0053] The temperature is raised twice for the second crystallization, and the material is discharged after the second crystallization at the second crystallization temperature of 98° C. for 2 hours, and the 13X molecular sieve product is obtained after separation, washing and drying. The crystallinity of the 13X molecular sieve product in Example 2 is 98.3%.

[0054] Example 3

[0055] The water glass with a concentration of SiO2: 15.29% and Na2O: 5.9% and the sodium aluminate solution with a concentration of Al2O3: 30.2g / L and Nk: 32.8g / L are synthesized according to a silicon-aluminum ratio of 2.65, and the synthetic alkali ratio is 2.7 to obtain a first sodium aluminosilicate gel slurry;

[0056] After the first crystallization at the first crystallization temperature of 70°C for 12 hours, the crystallinity was 79.5%. A sodium hydroxide solution with a concentration of Na2O: 103.2 g / L was added to adjust the synthetic alkali ratio to 3.2 to obtain a second sodium aluminosilicate gel slurry;

[0057] The temperature is raised twice for the second crystallization, and the material is discharged after the second crystallization at the second crystallization temperature of 98° C. for 2 hours, and the 13X molecular sieve product is obtained after separation, washing and drying. The crystallinity of the 13X molecular sieve product in Example 3 is 95.6%.

[0058] Comparative Example 1

[0059] The water glass with a concentration of SiO2: 16.79% and Na2O: 5.5% and the sodium aluminate solution with a concentration of Al2O3: 92.3g / L and Nk: 119.7g / L are synthesized according to a silicon-aluminum ratio of 2.0, and the synthetic alkali ratio is 2.7 to obtain a first sodium aluminosilicate gel slurry;

[0060] After crystallization at a crystallization temperature of 70°C for 4 hours, the temperature was raised again, and after crystallization at a crystallization temperature of 87°C for 3 hours, the product was discharged, separated, washed, and dried to obtain a 4A molecular sieve product. The crystallinity of the 4A molecular sieve product in Comparative Example 1 was 82.3%.

[0061] Comparative Example 2

[0062] The water glass with the concentration of SiO2: 15.29%, Na2O: 5.9% and the sodium aluminate solution with the concentration of Al2O3: 30.2g / L, Nk: 32.8g / L are synthesized according to the silicon-aluminum ratio of 2.8, and the synthetic alkali ratio is 2.8 to obtain the first sodium aluminosilicate gel slurry;

[0063] After crystallization at a crystallization temperature of 70°C for 12 hours, the temperature was raised again, and the material was discharged after crystallization at a crystallization temperature of 87°C for 2 hours, and the 13X molecular sieve product was obtained after separation, washing and drying. The crystallinity of the 13X molecular sieve product in Comparative Example 2 was 86.5%.

[0064] Through the analysis of the above-mentioned Examples 1 to 3 and the comparative examples, since the molecular sieve consumes a large amount of alkali during the crystallization process, that is, the residual alkali concentration in the mother liquor decreases as the crystallization proceeds, resulting in the problem of insufficient crystallization power due to the decrease in alkali concentration in the later stage of crystallization, affecting the improvement of the crystallinity of the 4A and 13X molecular sieve products. Therefore, when the first sodium aluminosilicate gel slurry is liquid-crystallized to the first crystallinity, alkali solution is added to the first sodium aluminosilicate gel slurry, thereby injecting new crystallization power into the first sodium aluminosilicate gel slurry system, thereby improving the crystallinity of the molecular sieve; the second sodium aluminosilicate gel slurry with the target alkali ratio undergoes a second crystallization, further providing crystallization power for improving the crystallinity, thereby obtaining 4A and 13X molecular sieves with high crystallinity; while Comparative Examples 1 and 2 do not provide the mother liquor with alkali concentration in time during the crystallization process, resulting in the problem of insufficient crystallization power due to the decrease in alkali concentration in the later stage of crystallization, and 4A and 13X molecular sieves with lower crystallinity are obtained.

[0065] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0066] (1) The method for improving the crystallinity of molecular sieves provided in the embodiments of the present application is simple and easy to implement, and can be widely used in the production process of 4A and 13X, and can stabilize the crystallinity of 4A and 13X molecular sieves at more than 90%;

[0067] (2) The method for improving the crystallinity of the molecular sieve provided in the embodiment of the present application is that when the crystallization process enters a certain stage of dissolution-crystallization (crystallization to a crystallinity of 75% to 80%), sodium hydroxide solution is added to the slurry according to a certain synthetic alkali ratio, thereby injecting new crystallization power into the slurry system, accelerating the dissolution-crystallization process, and the crystallinity of the molecular sieve will be greatly improved;

[0068] (3) The method for improving the crystallinity of the molecular sieve provided in the embodiment of the present application does not require any changes to the molecular sieve production process, but only requires adjustments to the crystallization process of the molecular sieve, and the process is simple and easy.

[0069] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for improving the crystallinity of molecular sieves, characterized in that: The method comprises: Performing a first crystallization on the first sodium aluminosilicate gel slurry until the crystallization reaches a first degree of crystallinity, and then adding an alkali solution to the first sodium aluminosilicate gel slurry to obtain a second sodium aluminosilicate gel slurry having a target alkali ratio; The second sodium aluminosilicate gel slurry is subjected to a second crystallization to obtain a molecular sieve.

2. The method according to claim 1, characterized in that The first crystallinity is 75% to 80%.

3. The method according to claim 1, characterized in that The second crystallization temperature is 95°C to 100°C.

4. The method according to claim 1, characterized in that: The first crystallization temperature is 80°C to 85°C.

5. The method according to claim 1, characterized in that The alkali solution includes sodium hydroxide solution.

6. The method according to claim 5, characterized in that The content of Na2O in the sodium hydroxide solution is 100g / L to 110g / L.

7. The method according to claim 1, characterized in that The molecular sieve includes the following: 4A molecular sieve and 13X molecular sieve.

8. The method according to claim 7, characterized in that If the molecular sieve is 4A molecular sieve, the target alkali ratio is less than 3.

0.

9. The method according to claim 7, characterized in that: If the molecular sieve is 13X molecular sieve, the target base ratio is less than 3.

5.

10. The method according to claim 1, characterized in that The method further comprises: The silicon source solution and the aluminum source solution are chemically reacted to obtain the first sodium aluminosilicate gel slurry.

Citation Information

Patent Citations

  • Synthetic method for preparing Beta zeolite

    CN103818919A

  • Modified CHA molecular sieve and preparation method and application thereof

    CN110665538A

  • Vanadium silicate molecular sieve and synthesis method and application thereof, and phenol oxidation method

    CN110961141A

  • ZSM-48 molecular sieve and preparation method thereof

    CN111137905A

  • Y-type molecular sieve and synthesis method thereof

    CN114735716A